Mapping Global Research Trends on Job Insecurity: A Bibliometric Analysis of Labor Force Transformation - Rahmat Hidayat; Syamsul Bahri (Forum Kerjasama Pendidikan Tinggi, 2026)
The available literature on job insecurity exists in various disciplines, using a variety of theoretical frameworks and indicators, thus giving rise to the need to systematically map the structure of knowledge and the direction of findings. This study aims to map the global development of research on job insecurity in the context of workforce transformation, especially due to digitalization, automation, organizational change, and psychological dynamics of workers. In addition, this study also identifies publication trends, key scientific actors, dominant countries, keyword relationships, as well as thematic clusters that make up the knowledge structure of this field. The method used is a bibliometric analysis based on Scopus data with the search keyword